Trends of “Tahfidz House” Program in Early Childhood Education - Ahmad Sabri (Jurnal Pendidikan Usia Dini, 2020)
The enthusiasm in the Tahfidz House (TH) education program especially for children shows an increasing trend in Padang, a modeling city in developing Islāmic character for children. The purpose of this study was to investigate the Tahfidz House program trends development in early childhood in Padang. This study uses qualitative methods with data collection tools, namely inter- views, direct observation, and document analysis. The results showed that: First, the Tahfidz House program attracted public interest because it offered dimensions of character formation such as in- creasing Intelligence Quotient, Emotional Quotient, and Spiritual Quotient. Second, there is a theo- logical reason in the landscape of local people to think that the Qur'an offers a blessing concept in our lives. Third, Tahfidz House existences as non-formal education has two dominant affiliations, namely pure education and based on market interests or capitalization. Keywords: Early Childhood Education, Tahfidz House Program, Market Interest Reference Abdullah, N. M. S. A. N., Sabbri, F. S. M., Athirah, R., & Isa, M. (2019). Challenges and Difficulties in Memorizing the Qurʾan in the Tahfiz Classes Among Secondary Learners. Al Burhan- Journal of Qurʾān and Sunnah Studies Kulliyyah of Islamic Revealed Knowledge and Human Sciences, 3(2), 1–14. Afriami, Z., & Rahmah, E. (2017). Pembuatan Direktori Rumah Tahfidz Quran se Kota Padang. Jurnal Ilmu Informasi Perpustakaan Dan Kearsipan, 6(September), 86–94. Ahmadi. (2018). Pembentukan Karakter Anak Dengan Pendekatan Berbasis Pendidikan Al- Qur ’ an. ALFIKR:Jurnal Pendidikan Islam, 4(1), 23–31. Akbar, Ali & Islmail, H. (2016). Metode Tahfidz Al-Qur‟An di Pondok Pesantren Kabupaten Kampar. Jurnal Ushuluddin, 24(1), 91–102. Al-fadhil, M. (2016). Mazhab Pendidikan Kritis; Proses Humanisasi Pendidikan. MUDARRISUNA (Media Kajian Pendidikan Agama Islam), 6(1), 33–52. Ali, Z. Z. (2017). Pemikiran Hegemoni Antonio Gramsci (1891-1973) di ITALIA. YAQZHAN, 3(2), 63–81. Ambo, N. F., & Mokhsein, S. E. (2019). Trend and Issue in Learning Strategy of Tahfiz Model Ulul Albab (TMUA). International Journal of Academic Research in Business and Social Sciences, 9(7), 1418–1426. https://doi.org/10.6007/ijarbss/v9-i7/6789Anwar, K., & Hafiyana, M. (2018). Implementasi metode ODOA (one day one ayat) dalam meningkatkan kemampuan menghafal al-qur‟an. JPII, 2, 181–198. Arief, A. (2014). Pengembangan pendidikan budaya dan karakter bangsa dalam upaya menghadapi tantangan global. TARBIYA: Journal of Education in Muslim Society, 1(2), 215-226. Azra, A. (2017). Surau; Pendidikan Islam Tradisional Dalam Transisi dan Modernisasi. Jakarta: Prenada Media. Baihaki, E. S. (2017). Penerjemahan Al-Qur’an: Proses Penerjemahan al-Qur’an di Indonesia. Jurnal Ushuluddin, 25(1), 44–55. Bashori. (2017). Modernisasi Lembaga Pendidikan Pesantren Perspektif Azyumardi Azra. Jurnal Pendidikan Islam, 11(2), 269–296. Basyit, A. (2019). Pengembangan Manajemen Rumah Tahfidz Al-Qur’an di Indonesia. Tadarus Tarbawy, Vol. 1(2), 163–180. Battersby, Paul, & Siracusa, J. M. . (2009). Globalization and Human Security. United States of America: Royman and Little Field Publisher. Ebrahimi, E. (2011). Spiritual Health and psychosis in the light of Quran. Arak Medical University Journal (AMUJ), 13(5), 1–9. Faturrahman, B. M. (2019). Pemikiran Kritis Sound Governave Terhadap Globalisasi: Pandangan Dari Ali Farazmand. Jurnal Politik Dan Sosial Kemasyarakatan, 11(2), 1689–1699. Firmansyah, R., Ismail, S., Utaberta, N., Yuli, G. N., & Shaari, N. (2020). Student’s Perception of Common Rooms in Daarut Tauhid Tahfidz Islamic Boarding School, Bandung. 192(EduARCHsia 2019), 86–89. https://doi.org/10.2991/aer.k.200214.012 George, R., & Goodman, D. (2012). Teori Sosiologi Modern. Jakarta: Kencana Prenada Media Group. Hambali, H. (2017). Globalisasi Dan Pendidikan Pesantren. At-Ta’lim: Media Informasi Pendidikan Islam, 13(2), 213-234. Hidayah, N. (2016). Strategi Pembelajaran Tahfidz Al-Qur’an di Lembaga Pendidikan. Ta’allum, 4(1), 63-81. Hoffman, J. (2007). A Glossary of Political Theory. Edinburgh: Edinburgh University Press. Indrioko, E. (2015). Membangun Citra Publik Dalam Lembaga Pendidikan Islam. UNIVERSUM (Jurnal Keislaman Dan Kebudayaan), 9(No 2), 265–274. https://doi.org/https://doi.org/10.30762/universum.v9i2.92 Karsidi, R. (2017). Budaya lokal dalam liberalisasi pendidikan. The Journal of Society & Media, 1(2), 19–34. Kirana, Z. C. (2017). Pandangan Azyumardi Azra Terhadap Modernisasi Pesantren. INOVATIF: Jurnal Penelitian Pendidikan, Agama Dan Kebudayaan, 3(1), 77–94. Latif, M. K., Jimaain, T., & Jasmi, K. A. (2020). Competence and Method of Teaching Tarannum Al-Quran Among Teachers of Special Class on Reading and Memorizing Al-Quran Skill (KKQ) in Johor. 400(Icream 2019), 249–253. https://doi.org/10.2991/assehr.k.200130.177 Lubis, A. M., & Ismet, S. (2019). Metode Menghafal Alquran Pada Anak Usia Dini di Tahfidz Center Darul Hufadz kota Padang. Aulad : Journal on Early Childhood, 2(2), 8–14. https://doi.org/10.31004/aulad.v2i2.30 Mahjoob, M., Nejati, J., Hosseini, A., & Bakhshani, N. M. (2016). The Effect of Holy Quran V oice on Mental Health. Journal of Religion and Health, 55(1), 38–42. https://doi.org/10.1007/s10943-014-9821-7 Majid, A. (2016). Strategi Pembelajaran. Bandung: Pt Remaja Rosdakarya. Malikah, N., Hidayatullah, F., Asrowi, & Anitah, S. (2020). Inside-Outside: Model of Memorizing Hadith at Elementary Islamic School. 422(Icope 2019), 386–390. https://doi.org/10.2991/assehr.k.200323.155 Marcuse, H. (2012). Perang semesta Melawan Kapitalisme. Jakarta: Gramedia. Moleong. (2017). Metode Penelitian Kualitatif (Vol. Cetakan 37). Bandung: Remaja Rosdakarya. Murniyati. (2017). Implementasi Pendidikan Karakter Religius terhadap Anak Usia Dini. Prosiding Seminar Nasional 20 Program Pascasarjana Universitas PGRI Palembang, (November). Muslimin, A. (2015). Implementasi Metode Halaqah dan Resitasi Dalam Tahfidz Al-Quran di SDIT el-Haq Banjarsari Buduran Sidoarjo. Jurnal Pendidikan Islam, (1), 55–62. Nawaz, N., & Jahangir, S. F. (2015). . Effects of memorizing Quran by heart (Hifz) on later academic achievement. Journal of Islamic Studies and Culture, 3(1), 58-64. Nugraheni, S., & Fakhruddin, F. (2014). Persepsi dan Partisipasi Orang Tua terhadap Lembaga PAUD Sebagai Tempat Pendidikan untuk Anak Usia Dini (Studi pada Orang Tua di Desa Tragung Kecamatan Kandeman Kabupaten Batang). Journal of Nonformal Education and Community Empowerment, 3(2). Nurani, Y., & Dwi, A. (2017). Early Childhood Education Teachers ’ Effective Communication Based Teaching Skill. Proceedings of the 9th International Conference for Science Educators and Teachers (ICSET 2017), 118, 723–728. Pieterse, J. N. (2019). Globalization and culture: Global mélange.: Rowman & Littlefield. Pramono, S. Y., & Sofyan, H. (2019). Quality Learning Tahfiz Design in Integrated Islamic Elementary School Sleman Special Region of Yogyakarta. 323(ICoSSCE 2018), 88–94. https://doi.org/10.2991/icossce-icsmc-18.2019.17 Priatna, T., Nurhamzah, Suryana, Y., & Nurdiansah, N. (2015). International Journal of Advanced Trends in Computer Science and Engineering Available Online at http://www.warse.org/ijatcse/static/pdf/file/ijatcse02422015.pdf. 4(2), 15–21. Rifki. (2017). Komersialisasi Pendidikan: Tantangan Bagi Lembaga Pendidikan Islam. I’tibar (Jurnal IlmiahIlmu-Ilmu Keislaman), 4(8), 167–182. Rosyid, M. Z. (2019). Kapitalisme Pendiidkan Islam (Antar Kompetensi dan Keadilan). Akademika:Jurnal Pendidikan, 2(1), 112–123. Rustiawan, H. (2015). Komersialisasi Pendidikan. Tazkiya (Jurnal Keislaman, Kemasyarakatan Dan Kebudayaan), 16(1), 44–63. Sa’diyah, R. (2013). Melatih Kecerdasan Emosi Anak Usia Dini. Jurnal Kependidikan., 18(1), 119–120. Samuel, P. H., & Conley, M. (2019). Dampak arus globalisasi terhadap jalannya demokrasi di indonesia. Juirnal Rectum, I(1), 104–114. Santrock, J. W. (2007). Perkembangan anak. Jakarta: Erlangga. Steger, M. B. (2017). Globalization: A very short introduction (Vol. 86). America: Oxford University Press. Sugiyono. (2017). Metode Penelitian Bisnis: Pendekatan Kuantitatif, Kualitatif, Kombinasi, dan R&D. Bandung: CV. Alfabeta. Sujiono, Y. N. (2009). Konsep Dasar Pendidikan Anak Usia Dini. Jakarta: Indeks.Tadjuddin, M. S., Sani, M. A. M., & Yeyeng, A. T. (2016). Dunia Islam dalam Lintasan Sejarah dan Realitasnya di Era Kontemporer. AL-FIKR V6, 20(2). Taslama. (2014). Keajaiban al-Quran. Surabaya: Penerbit Sygma. Tidjani, A. (2017). Manajemen Lembaga Pendidikan Islam Menghadapi Tantangan Globalisasi. Jurnal Reflektika, 13(1), 96–126. https://doi.org/10.28944/reflektika.v13i1.74 Utama. (2016). Pembumian Jihad dalam Konteks Indonesia Kekinian: Pengentasan Masyarakat dari Kemiskinan dan Keterbelakangan. Jurnal Multikultural & Multireligius, 53. van Glinken, H. (2014). Globalization, Higher Education and Sustainable Development. European Union Rectors’ Conference. Kuala Lumpur: Ministry of Higher Education of Malaysia, University of Malaya, Delegation of the European Commission in Malaysia, and Asean – European Union Network Programme. Yusuf, M. (2017). Pendidikan karakter, Konsep Dan Aplikasinya Pada Sekolah Berbasis Agama Islam. Intizam, Jurnal Manajemen Pendidikan Islam, 1(1), 14–22. Zulfitria. (2017). Peranan Pembelajaran Tahfidzal-Quran Dalam Pendidikan Karakter Di Sekolah Dasar. Naturalistic: Jurnal Kajian Penelitian Pendidikan Dan Pembelajaran, 1(2), 124– 134.